الشّنفرى - في لاميته- بين نزعة التّمرد والاعتداد بالذّات الإنسانيّة - قادرة, غيثاء (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
شكّلت حركة الصّعاليك الشّعرية أول حركة تمرد في تاريخ الشّعر العربي؛إذ شقّ هؤلاء الصّعاليك، ومن بينهم الشّنفرى، عصا الطّاعة، وخرجوا على العرف الشّعري الجاهلي، متمردين، مغيرين ، ثائرين ، ساعين إلى التّقويم وقهر الاغتراب، وتمرّد الشّنفرى ما هو إلاّ تعبير عن خلجات النّفس الرّافضة الظّلم، والرّاغبة في الانتقام. إنّه تمرّد مازجه اعتداد بالذّات الإنسانيّة والمتصارعة مع المجتمع، المتنازعة معه ؛لإثبات الوجود، وتجربة الشّنفرى تجربة فريدة تتّصل بموقف التمرد والاغتراب، ذلك الموقف الذي يمثل واحداً من المواقف الإنسانيّة الأساسيّة في مواجهة الوجود والمجتمع . The poetic rebels movement was the first rebellious movement in the history of the Arab poetry، when those rebels declared their disobedience and denied the jahili poetic tradition، revolting، assaulting، addicting to adjust things and defeat the alienation. And the rebellion Shanfara made was not but an expression of self impulses، which refused the injustice and tended to revenge from injustice. It is a rebellion mixed with human self-assertion، contesting with society to confirm one's own existence. And the experience of Shanfara is a unique one with relevance to alienation and rebellion attitude، an attitude that presents one of basic human ones against society.